Tropical viral infections - Smith, David W. (Pathology, 2012)
Travel into subtropical and tropical areas is increasing, with a corresponding increase in the number of suspected viral infections acquired while travelling. In addition, legal and illegal immigrants may enter with overseas-acquired infections. Some of these infections are endemic to Australia, but are seen more often in returned travellers because they are more common overseas. These include hepatitis A, hepatitis B, HIV, seasonal influenza, measles, mumps and rubella. In addition there are number of infectious agents that are exotic or uncommon within Australia and are a particular diagnostic concern in people recently arrived from overseas. The most important of these are dengue virus infections, which have been increasing internationally in recent decades. Other arboviruses such as chikungunya and Japanese encephalitis virus also require consideration. Other important but rare viruses include Nipah virus, hantaviruses, rabies virus and the viruses causing viral haemorrhagic fever. Also it is important to consider new pathogens, as Asia has seen the emergence of SARS coronavirus, avian influenza virus, Nipah virus and others in recent years. This talk will focus on the exotic viruses and the diagnostic approach to potential overseas-acquired viral illnesses.